2010
DOI: 10.1177/003335491012500615
|View full text |Cite
|
Sign up to set email alerts
|

The National Asthma Survey—New York State: Association of the Home Environment with Current Asthma Status

Abstract: Asthma guidelines emphasize the importance of reducing triggers in the home as part of a multifaceted approach to asthma control. Despite these guidelines, many asthma triggers (specifically, mold) were as prevalent or more so in the homes of New Yorkers with asthma as compared with control households. Public health interventions in NYS should focus on educating households about potential asthma triggers and their sources and teach methods to prevent, reduce, or eliminate them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 23 publications
1
24
0
3
Order By: Relevance
“…Studies performed in Copenhagen [35], and New York State [36], for example showed no association between asthma and use of gas stoves. A survey that included not only adults, but also children, was conducted in Iran where traditional Persian stoves are used.…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed in Copenhagen [35], and New York State [36], for example showed no association between asthma and use of gas stoves. A survey that included not only adults, but also children, was conducted in Iran where traditional Persian stoves are used.…”
Section: Resultsmentioning
confidence: 99%
“…The National Asthma Survey found an association between asthma in children and humidifier use, 48 the health effects of which have been termed "humidifier fever." 49 Proper maintenance or avoidance of cool mist or ultrasonic humidifiers is essential to prevent such effects.…”
Section: Interventionsmentioning
confidence: 99%
“…A direct association was identified among the presence of mold (adjusted OR, 2.5; 95% CI, 1.8e3.4), air cleaners (adjusted OR, 2.2; 95% CI, 1.7e2.8), humidifiers (adjusted OR, 1.4; 95% CI, 1.1e1.8), and current asthma. 88 Another study in the United Kingdom demonstrated that adults both sensitized and exposed to high levels of sensitizing allergens had significantly lower predicted FEV1% (mean, 83.7% vs. 89.3%; p Z 0.03), higher FeNO values (GM, 12.8 ppb vs. 8.7 ppb; p Z 0.001), and more severe airway reactivity (PD 20 GM, 0.25 mg vs. 0.73 mg; p < 0.001) compared with unsensitized and unexposed individuals. 89 A recent Swedish study examined if exposure to indoor allergens was associated with allergic sensitization prevalence.…”
Section: Relationships Between Asthma and Asthma-related Symptoms Andmentioning
confidence: 99%